A new direction in engineering mathematics: integrating mathematical thinking and engineering thinking - Abdul Rahman, Roselainy (2013)
This paper describes a proposal to enhance the teaching of Engineering Mathematics by integrating mathematical thinking and engineering thinking. In our previous research we had focused on the development and support of the mathematical thinking amongst engineering undergraduates and the results showed that the strategies we used were successful in promoting positive changes in our attitude as well as that of our students. However, the transfer of knowledge remains problematic since the application of the mathematics learnt to the specific engineering discipline was done in a general manner. Here, the emphasis will be on how mathematics can be better integrated into engineering education to support the flexible thinking skills that are critical for engineering practice broadly as well as for creativity and innovation. We will present a conceptual framework on the importance of making both thinking processes explicit which would positively influence the teaching of mathematics to prospective engineers.